The Unexpected Experience: Positive Minority Perceptions and Experiences of Policing - Bediako, Geremy (Université d'Ottawa / University of Ottawa, 2017)
For as long as Black men and police officers have co-existed in North America, tensions have persisted between the two groups. Issues of racial profiling, racial discrimination and other forms of racism have plagued Black men’s experiences and perceptions. Currently, tensions between these two groups have been high resulting in the emergence of social activist groups, such as Black Lives Matter. Most of what is known about race and policing tends to focus on Black men, policing and its negative aspects. However, in addition to examining and studying the negative aspects, there is a need to provide discussion on the potential positive aspects. Little is known about the processes through which Black men identify and determine the positive elements that constitute a positive experience. This is a perspective that has not been explored in depth in the literature concerning policing and race in Canada. The present study addresses the gaps in the existing literature by conducting a thematic analysis of 10 in-depth interviews with Black Torontonian men. In doing so, the interview gives voice to Black men by having them identify the elements of a positive and negative experience, and by providing clues to police and Black men’s interactions in Canada. Drawing upon symbolic interactionist concepts, this study provides a Black perspective on the processes for Black men’s daily interactions with police officers. Policy implications based on the findings section are presented at the end of the study, in addition to directions for future research.
Keywords: Race; Policing